2011
DOI: 10.1111/j.1442-200x.2010.03189.x
|View full text |Cite
|
Sign up to set email alerts
|

Benign and malignant tumors in Down syndrome: Analysis of the 1514 autopsied cases in Japan

Abstract: We present new associations of benign and malignant tumors with Down syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…The low rate of breast cancer among women with DS included in our study is consistent with low rates of breast cancer reported in previous studies (e.g., Ehhara et al, 2011;Hasle et al, 2000;Hermon et al, 2001;Satge et al, 2001;Sullivan et al, 2007). We found only two cancers; one being a noninvasive ductal adenocarcinoma in situ and one a phyllodes tumor with borderline malignant potential.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The low rate of breast cancer among women with DS included in our study is consistent with low rates of breast cancer reported in previous studies (e.g., Ehhara et al, 2011;Hasle et al, 2000;Hermon et al, 2001;Satge et al, 2001;Sullivan et al, 2007). We found only two cancers; one being a noninvasive ductal adenocarcinoma in situ and one a phyllodes tumor with borderline malignant potential.…”
Section: Discussionsupporting
confidence: 92%
“…Although 7.3 cases were expected based on data from the general population, no cases of breast cancer were identified from the 2,814 Danish individuals with DS (Hasle et al, 2000). Similar findings have been reported with Australian (Sullivan et al, 2007), Japanese (Ehhara et al, 2011), and Finnish women with DS (Patja et al, 2006).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…There were eight cases of benign tumours. Only pancreatic tumour was reported, and this was a pancreatic islet cell adenocarcinoma at the age of 45 years (12). …”
Section: Discussionmentioning
confidence: 99%
“…However, Asian patients with DS do not have a lower risk of brain tumors, especially germ cell tumors [2]. Satge et al summarized 38 central nervous system tumors in DS and reported that 14 (61%) of 23 cases under age 15 were germ cell tumors [3].…”
Section: Introductionmentioning
confidence: 99%